2014
DOI: 10.1002/ajpa.22552
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multidimensionality of stature variation in the past through comparisons of archaeological and living populations

Abstract: Adult stature variation is commonly attributed to differential stress-levels during development. However, due to selective mortality and heterogeneous frailty, a population's tall stature may be more indicative of high selective pressures than of positive life conditions. This article examines stature in a biocultural context and draws parallels between bioarchaeological and living populations to explore the multidimensionality of stature variation in the past. This study investigates: 1) stature differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 70 publications
(107 reference statements)
2
91
0
5
Order By: Relevance
“…In a comparative study of stature variation between archaeological samples and living people, Vercellotti et al (2014) found that modern populations generally enjoyed less physiological stress than individuals from the Medieval period. Therefore, the individuals from the ArtiVarK study are suspected to be of better health and nutrition due to current living standards in the Netherlands, as well as their significantly taller stature.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative study of stature variation between archaeological samples and living people, Vercellotti et al (2014) found that modern populations generally enjoyed less physiological stress than individuals from the Medieval period. Therefore, the individuals from the ArtiVarK study are suspected to be of better health and nutrition due to current living standards in the Netherlands, as well as their significantly taller stature.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…Therefore, the individuals from the ArtiVarK study are suspected to be of better health and nutrition due to current living standards in the Netherlands, as well as their significantly taller stature. However, as Vercellotti et al (2014) rightfully point out, stature might not be the best indication for health per se. Nonetheless, there is no specific information available on general and specific stress markers (influence of possible diseases/impairments) for the individuals from the ArtiVarK sample.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…If our results suggest that the skeletons with TB lesions also show signs of stunting or wasting, we could infer that they are due to a long-lasting active TB phase, and an estimate of its duration will be attempted. In fact, finding skeletal properties that are more compatible with a younger age class would provide a rough estimate of when the disease began compromising the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Several studies demonstrate a relationship between early disturbances in growth due to infectious disease and malnutrition, and attained stature (Vercellotti et al, 2014, and references therein) and body proportions (Robbins Schug, 2011). Numerous factors including catch-up growth and selective mortality warn against making simplistic inferences about the environmental conditions of a population from average stature (Wood et al, 1992;Vercellotti et al, 2014).…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…Early disturbances in growth due to infectious disease and malnutrition may prevent the attainment of full stature potential (Robbins Schug, 2011;Vercellotti et al, 2014). Both AC5 and AQ1 display statures that are at the lower end of the range of variation for their age/sex class, but they do not appear to be severely stunted in growth.…”
Section: Body Size and Proportionsmentioning
confidence: 99%
“…This method does not rely on calculating stature from a single long bone using regression formulae (the “mathematical method”), but instead produces an estimate based upon the measurement of all of those bones that contribute to height (Raxter et al, 2006, 2007; Maijanen, 2009; Auerbach and Ruff, 2010; Auerbach, 2011; Vercellotti et al, 2014). This provides a more accurate method of calculating living stature, as it is not biased by differences in bodily proportions (Maijanen, 2009; Auerbach and Ruff, 2010; Vercellotti et al, 2014). As studies of stature are increasingly beginning to incorporate vertebral components, it is also now prudent to consider the growth of these skeletal elements.…”
Section: Research Rationalementioning
confidence: 99%